How many molecules are required to obtain a steady faradaic current from mediated electron transfer at a single nanoparticle on a supporting surface? - Kätelhön, E; Krause, K; Wolfrum, B; Compton, R (2014)
We investigate the chronoamperometric noise characteristics of electron-transfer reactions occurring on single nanoparticles (NPs) and assemblies of well-separated NPs on a supporting surface. To this end, we combine a formerly described expression for the steady-state current of a single particle with the shot-noise model and derive an expression for the signal-to-noise ratio as a function of bulk concentration and particle radius. Our findings are supported by random-walk simulations, which closely match the analytical results.